Synthesis of Zinc Borate: Effects of Different Modifying Agents and Isopropyl Alcohol on Yield and Hydrophobicity by Using Zinc Carbonate - Tugrul, Nurcan; Acarali, Nil Baran (INT ASSOC COMPUTER SCIENCE & INFORMATION TECHNOLOGY PRESS-IACSIT PRESS, 2011)
In this study, the aim of this study was to synthesize zinc borate by using different modifying agents and isopropyl alcohol in the presence of zinc carbonate, reference boric acid and seed. The experiments were carried out by dissolving of boric acid in a glass beaker in distilled water. Temperature is controlled using a digital temperature sensor and magnetic stirrer provides constantly stirring during the reaction. The effects of modifying agents and isopropyl alcohol on hydrophobicity were investigated. As a result, the analysis results showed that the usage of modifying agents with isopropyl alcohol affected the hydrophobicity of zinc borate and zinc borate which was successfully synthesized has been observed with Xray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FT-IR) analysis that was carried out after experiments.
Keywords: zinc carbonate; hydrophobicity; modifying agent; zinc borate; Engineering